Fintech Services In Financial Inclusion In Jeranglah Rendah Village, South Bengkulu Regency - Pongki Resmala Puteri; Kresnawati Kresnawati; Iswidana Utama Putra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the role of financial technology (fintech) services in financial inclusion in Jeranglah Rendah Village, South Bengkulu Regency. This research employed a descriptive quantitative method using a survey approach with questionnaires distributed to 60 respondents who are active users of fintech services. The results show that fintech services have a positive and significant impact on improving access, usage, and quality of financial services in rural communities. Fintech simplifies transactions, expands access to formal financial institutions, and enhances economic efficiency. However, challenges remain, such as limited digital infrastructure and low financial literacy among some villagers. The findings highlight the importance of fintech as a digital tool to accelerate financial inclusion in rural areas and emphasize the need for government support in improving digital literacy and financial infrastructure.